Profile of Drug Adherence in Elderly Patients with Oral Antidiabetes And Antihipertensive Therapy Using Pill Count Method: Profil Kepatuhan Minum Obat Pasien Lansia Dengan Terapi Oral Antidiabetes Dan Antihipertensi Metode Pill Count - Ninik Mas Ulfa (Akademi Farmasi Surabaya, 2023)
Medication adherance is a problem by the elderly. This study was conducted to evaluate adherence to taking oral antidiabetic drugs and oral antihypertensive drugs in elderly patients using the pill count method at one of the health centers in South Surabaya. The pill count method in this study was chosen because it can provide an overview of the profile of medication adherence for elderly patients who receive oral antidiabetic and oral antihypertensive drugs by calculating the remaining medication based on the dosage and the rules for taking the drug when the patient returns to control. This study was observational with prospective observations and data were analyzed descriptively. The number of samples in this study were 30 elderly patients. The results obtained were that the most oral antidiabates drugs were given the Sulfonylurea combination Biguanida drug class, namely Glibenclamide 5 mg combination Metformin 500 mg (66.7%), while for oral antidiabates therapy the single administration was the calcium channel blocker is Amlodipine 5 mg (76 %). In the results of medication adherence, it was found that 63.3% of patients adherance to taking oral antidiabetic drugs and not adherance is 36,7%. While 70.0% of patients were adherence to taking oral antihypertension drugs and not adherance is 30%. Patients who consumed 2 drug combinations were 53.3% more adherent than those who consumed 3 to 5 drug combinations of 46.7%.